2014
DOI: 10.1111/sji.12167
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and its Prognostic role in Post‐cardiac Arrest Patients

Abstract: Cardiac arrest causes generalized ischaemia/hypoxia, and subsequent resuscitation inflicts reperfusion injury, the pathology of which is not fully understood. Moreover, predicting the prognosis of comatose, post-cardiac arrest patients is a complex clinical challenge. We hypothesized that the extent of complement activation might be a reliable predictor of mortality in this population. Forty-six comatose cardiac arrest patients were enrolled into our prospective cohort study, conducted in a tertiary care unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
2
11
0
1
Order By: Relevance
“…Targeted temperature management is suggested to reduce complement activation . We found higher levels of MASP‐2 and MASP‐3 and lower levels of M‐ficolin in the prolonged group compared with the standard group.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Targeted temperature management is suggested to reduce complement activation . We found higher levels of MASP‐2 and MASP‐3 and lower levels of M‐ficolin in the prolonged group compared with the standard group.…”
Section: Discussionmentioning
confidence: 73%
“…Bisschops et al observed that rewarming after cardiac arrest was followed by increasing levels of inflammation products, including C3a and MAC. Furthermore, Jenei et al found that a higher C3a/C3 ratio, a measure of complement activity, was associated with poor survival. In the present study, we found that rewarming was followed by significant increases in MASP‐3 levels (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used assay for assessment of soluble C4d is manufactured by Quidel and has been used in a number of clinical studies regarding vasculitis (Gou et al, 2013), cardiac arrest (Bisschops et al, 2012) (Jenei et al, 2014), graft rejection (Flechner et al, 2010), mixed cryoglobulinemia (Sansonno et al, 2009), Sjögren's syndrome (Sudzius et al, 2014), lupus (Manzi et al, 1996) and lung cancer (Ajona et al, 2013). According to the manufacturer, this ELISA is based on a neoepitope C4d catching antibody and detection is completed by goat polyclonal anti-C4d.…”
Section: Impact Of Temperature Alterations On C4d Detection By This Nmentioning
confidence: 99%
“…Ismert, hogy az újraélesztés utáni korai szakban megemelkedik a prokalcitonin szintje, ez azonban az újraélesztés utáni szisztémás reperfúziós válasz súlyossá-gával és nem a korai infekció megjelenésével korrelál [27]. A hypoxiás inzultus következtében megemelkedik a komplementaktivitás is, aminek laborkémiai markerként a jövőben a prognózisbecslésben lehet szerepe [28].…”
Section: A Terápiás Hypothermia Mellékhatásai éS Potenciális Szövődméunclassified